Pheromone Production, Attraction, and Interspecific Inhibition among Four Species of Ips Bark Beetles in the Southeastern USA - Göran Birgersson; Mark J. Dalusky; Karl E. Espelie; C. Wayne Berisford (Psyche: A Journal of Entomology)
Hindgut volatiles from attacking, unmated males of Ips avulsus, I. calligraphus, I. grandicollis, and I. pini were analyzed by combined gas chromatography and mass spectrometry. Based on the quantitative identifications of hindguts and subsequent individual aerations, baits were formulated and a combined species-specific subtractive field bioassay was set up for the four bark beetle species. The bioassays were subtractive for the compounds identified in the hindgut analysis of each species, and volatiles identified in sympatric species were added as potential inhibitors alone and in combination. The trap catches from this bioassay revealed strong interspecific inhibition. The subtractive assays showed that I. grandicollis and I. calligraphus share (–)-(4S)-cis-verbenol as one pheromone component, while their second, synergistic pheromone component, (–)-(S)-ipsenol in I. grandicollis and (±)-ipsdienol in I. calligraphus, acts as an interspecific inhibitor to the other species. I. avulsus and I. pini were found to have very similar production of hindgut volatiles, and both use ipsdienol and lanierone as synergistic pheromone components. No beetle-produced interspecific inhibitor was identified between these two species. Lanierone was found to be an interspecific inhibitor for both I. calligraphus and I. grandicollis.